Spatial Distribution of Market Centers - Islam, Md. Morshedul (Universitas Prasetiya Mulya, 2017)
The present study is attempt to find the location pattern, distribution and their sphere of influences of market centers in Rangpur City Corporation, Bangladesh. Rangpur is facing some problems like traffic jam, noisy environment, population pressure etc due to the over population in full day long in the centre of this city, all of the whole sale and retail sale markets are located in the middle. Location of Market is always influencing the daily life of the city population who are directly or indirectly connected with the market. If the market strategically distributed in an area they don’t faces such kind of problems. Analysis or investigation shows that, at about all of the market centers are located in the center of Rangpur and in the residential area of Rangpur. The maximum 67% market centers are found in the high income residential area. Rangpur City Corporation, Bangladesh Bureau of Statistics and survey of Bangladesh provided the maps, reports and relevant documents of the study. The spatial dispersion pattern of market centers is clustered together at one place 0.33(Nearest Neighbor Index value, R) found in the study area. Geographical Information System (GIS) andother software also used to analyze the maps and diagrams. Investigation refers that, market of Rangpur city have a clustered pattern and different levels of market centers found on the bases of centrality scores. By this centrality scores or levels, found the variation of influencing spheres of market centers in Rangpur City.